RELIGIOUS ORGANIZATIONS AND CONFLICT RESOLUTION IN NIGERIA: AN EXAMINATION OF JAMA’ATU NASRIL ISLAM IN NORTHWEST NIGERIA (1999–2025) - Nasir, Bilkisu Muhammad; Garba, Dimas (Veredas do Direito, 2026)
This study examined the role of Jama’atu Nasril Islam (JNI) in conflict resolution in Northwest Nigeria from 1999 to 2025. The study was motivated by the increasing incidence of ethno-religious conflicts, banditry, communal violence, and insecurity in Northern Nigeria, alongside the growing involvement of religious organizations in peacebuilding processes. The study adopted a qualitative research design using interviews and documentary analysis as sources of data collection. Findings revealed that JNI plays significant roles in mediation, interfaith dialogue, humanitarian interventions, peace sensitization, reconciliation, and community mobilization in conflict-affected communities. The study further found that JNI utilizes dialogue, Sulhu mediation mechanisms, peace education, and collaboration with traditional rulers and security agencies in resolving disputes and promoting peaceful coexistence. However, challenges such as political interference, inadequate funding, and perceptions of religious bias constrain its effectiveness. The study concludes that religious organizations remain important non-state actors in peacebuilding and recommends stronger institutional support, interfaith collaboration, and inclusive community-based peacebuilding strategies in Nigeria.